Heroine in the Movie Wonder Woman (2017) - Nasrum; Kurnia; Taufik, Muhammad (Talenta Publisher, 2026)
This research analyzes the representation of the heroine in the movie Wonder Woman (2017) directed by Patty Jenkins by applying Maureen Murdock’s theory of The Heroine’s Journey (1990). The study examines how the main character, Diana Prince, reflects the stages of the heroine’s journey and embodies female empowerment within a patriarchal society. The movie presents a woman who’s strong, courageous, compassionate, and morally conscious, offering a perspective on heroism that integrates feminine and masculine values. This research employs qualitative descriptive method. The primary data are taken from the dialogues and scenes of Wonder Woman (2017), while the secondary data come from books, journals, and previous studies related to feminism, gender representation, and literary theory. The analysis is conducted using the eight stages of Murdock’s model: separation from the feminine, identification with the masculine, road of trials, illusory boon of success, spiritual aridity, initiation and descent, reconnection with feminine, and integration of masculine and feminine. The findings show that Diana Prince undergoes all stages of the heroine’s journey. She begins by leaving Themyscira and her mother, symbolizing separation from the feminine world. She later adopts masculine traits through battle and leadership but realizes that physical strength alone cannot create peace. After experiencing loss and despair, she reconnects with feminine values such as empathy and love as her true sources of power. In the end, she integrates both aspects, achieving balance and completeness as a heroine. This research concludes that Wonder Woman (2017) effectively represents modern female heroism that challenges patriarchal norms.